Identification of regions associated to the late blight resistance and viruses in potato germplasm using molecular markers - Vegas García, Ariadne; Sandrea Rincón†, Yanet; Zambrano†, Asia; González, Lourdes; Osorio, Martha; Trujillo, Guillermo; Peralta Calle, Jorge (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The combination of traits of economic interest in new potato cultivars, such as resistance to late blight, viral diseases, and culinary quality are important to achieve their adoption by farmers. In the present work, molecular markers were used to identify regions associated to late blight, the viruses PVY and PLRV resistance, in 50 materials belonging to the National Institute of Agricultural Research (INIA-Venezuela): commercial cultivars, differentials of blight, advanced clones from CIP and hybrids from the Fundación PROINPA of Bolivia. DNA extraction was carried out from vitroplants and known microsatellite, SCAR and CAPS molecular markers were used. Among 96 to 26% of the accessions amplified regions of the QTL tbr of chromosome XII, associated with resistance to blight. Only the differential R9 and crc2/P8 from PROINPA amplified the R1 gene region. Between 18 and 68% of the genotypes presented the regions associated with the PVY and PLRV resistance genes (Ryadg and N genes), respectively; only 10% amplified both regions; while in 24% these genes were not detected, among them are the commercial varieties Granola, Andinita and Cartayita. This study generated valuable information to support genebank curators and breeders in potato genetic improvement programs of this country.